Gender differences in job satisfaction: a case study at MOSTI/ Nurliyana Mohd Shazali and Muhamad Fuad Abdul Karim - Mohd Shazali, Nurliyana; Abdul Karim, Muhamad Fuad (2010)
Job satisfaction can be described as a pleasurable moment enjoyed by any employee in conducting his or her job; shown by his or her attitude. It is imperative for public organisations to acknowledge this issue since it will affect the employees’ performance and productivity. Job satisfaction can happen on any employee, regardless of gender. Overall, there is no significant difference between male and female officers in MOSTI in terms of their job satisfaction. Nevertheless, these officers have provided contrary perspectives on the facets that have influence their happiness at their workplace. This paper will discuss the gender differences in job satisfaction among the officers in MOSTI, Putrajaya, via looking at the overall perspectives, as well as at the facets of job satisfaction.